Analisis Pengaruh Pelatihan Resusitasi Jantung Paru RJP Dewasa terhadap Retensi Pengetahuan dan Ketrampilan RJP pada Mahasiswa Keperawatan di Yogyakarta - Linda Widyarani (Department of Nursing Universitas Jenderal Soedirman, 2017)
ABSTRACT Cardiac arrest is a major public health problem affecting thousands of individuals each year in both out-of-hospital and in-hospital setting. High quality of cardiopulmonary resuscitation (CPR) provide return of spontaneous after cardiac arrest, but majority of nursing students feel unconfident to practice CPR. The aim of the study was to assess the effect of CPR training program on knowledge and practices of nursing students in Yogyakarta. The study design was quasi-experimental and one group pretest - posttest design. A questionnaire was applied to the students before CPR training, then the student were informed about adult CPR by the researchers and all of the students practice CPR on a Resusci-Anne manikin. One months after this training the same questionnaire and skills checklist of CPR were apllied. Sixty five students of nursing participated in this study. This study show CPR training significantly positive impact cognitive and skills performance in nursing students. While the average CPR knowledge score of these students was 44,43%, before CPR training, this average increased to 89,64% after CPR training and decreased to 77,54% after one month CPR training. Skill score of the students one month after the CPR skill training was 70,61%. Nursing students tend to forget theoretical and applied CPR training after one month. Hence there is a need for continuous CPR training and education and repeating the skills at regular intervals ever after they have graduated to ensure sustainability in the CPR skills. Keywords : cardiopulmonary resuscitation, bystander CPR, training   ABSTRAK Henti jantung merupakan penyebab kematian utama pada kasus kegawatdaruratan kardiovaskuler, baik pada setting prehospital (OHCA) maupun intrahospital. RJP yang berkualitas dapat mengoptimalkan return of spontaneous circulation pada OHCA, tetapi banyak mahasiswa keperawatan tidak percaya diri dalam melakukan prosedur ini sehingga mereka membutuhkan pelatihan RJP, agar dapat berespon cepat, tanggap dan akurat dalam memberikan pertolongan pada korban OHCA. Penelitian ini menguji pengaruh pelatihan RJP dewasa terhadap retensi pengetahuan dan ketrampilan RJP pada mahasiswa keperawatan di Yogyakarta. Jenis penelitian quasi experimental dengan design one group pretest - posttest. Posttest diberikan dua kali, yaitu sesaat sesudah pelatihan dan sebulan sesudah pelatihan. Jumlah sampel yaitu 65 orang. Analisa data menggunakan pair t-test. Hasilnya, pelatihan RJP berpengaruh positif terhadap pengetahuan dan ketrampilan bystander RJP dengan p-value 0,000 (<0,001). Rerata skor awal pengetahuan 44,43%, rerata skor sesaat sesudah pelatihan 89,64% dan rerata skor sebulan sesudah pelatihan adalah 77,54%. Rata-rata skor ketrampilan sebelum pelatihan adalah 35,55%, rerata skor sesaat setelah pelatihan 91,80% dan rerata skor sebulan setelah pelatihan 70,61%. Penurunan retensi pengetahuan dan ketrampilan mahasiswa sebulan sesudah pelatihan RJP kemungkinan disebabkan karena mahasiswa kurang terpapar kasus pasien dengan henti jantung yang membutuhkan tindakan RJP. Kata Kunci: resusitasi jantung paru, pelatihan, bystander RJP